Care of water polo players - Stromberg, J. D. (Current Sports Medicine Reports, 2017)
Water polo is a team sport that combines swimming with overhead throwing and wrestling. This places water polo players at risk for a unique group of illnesses and injuries. In addition to the medical problems and injuries seen in competitive swimmers, water polo players are at risk for a variety of traumatic injuries, including concussions, eye injuries, tympanic membrane perforation, fractures, dislocations, and lacerations. Repetitive overhead throwing also places these athletes at risk for related injuries, such as shoulder problems, including rotator cuff strain and impingement, and elbow problems, such as ulnar collateral ligament injuries, posteromedial impingement, and osteochondritis dissecans of the radial capitellum. This article serves as an overview of these illnesses and injuries, as well as how the aquatic environment affects pathogenesis, treatment, and return to play.